THE IMPACT OF TECHNOLOGICAL CREATIVITY AND ENTREPRENEURSHIP EDUCATION ON THE ENTREPRENEURSHIP INTENTIONS OF STUDENTS AT PARTICULAR TERTIARY INSTITUTIONS IN ZIMBABWE AND SOUTH AFRICA - NDOFIREPI, TAKAWIRA MUNYARADZI (Bloemfontein: Central University of Technology, Free State, 2016)
This study explores the collective influence of technological creativity (TC) and exposure to entrepreneurship education (EE) on the entrepreneurship intentions (EI) of students at particular tertiary institutions in Zimbabwe and South Africa. Drawing on a positivist epistemology, a quantitative case study and total percentage analysis of tertiary education students who were randomly selected from the entrepreneurial programmes at the Central University of Technology, Free State (South Africa) and Kwekwe Polytechnic College (Zimbabwe), the study examines the extent to which these students intended to engage in entrepreneurship careers in the near future. Self-administered questionnaires were used to collect data from respondents. Out of a total of 400 questionnaires which were distributed to students enrolled for entrepreneurship courses at the two campuses, 284 were completed and returned, representing an overall response rate of 71%. A non-parametric test, the Mann-Whitney U test, was employed to establish whether there are any significant differences in the level of entrepreneurship intentions between South African and Zimbabwean tertiary education students. Another non-parametric technique, the Spearman Correlation, was employed to assess the relationships between technological creativity and entrepreneurship education on the one hand, and the direct determinants of entrepreneurship intentions and actual entrepreneurship intentions, on the other. The same technique was also used to assess the relationships between the immediate determinants of entrepreneurship intention and actual entrepreneurship intentions. Multiple regression analysis was conducted to test a number of predictive effects. Firstly, it was used to test the predictive effect of entrepreneurship education and technological creativity on the immediate determinants of entrepreneurship intentions. Secondly, it was used to assess the predictive effects of the immediate precursors of entrepreneurship intentions on the actual entrepreneurship intentions. Lastly, it tested the direct effects of entrepreneurship education and technological creativity on actual entrepreneurship intentions. The results demonstrate that although a majority of the Zimbabwean and South African respondents intended to engage in entrepreneurship in the near future, there were no significant differences in the levels of entrepreneurship intentions amongst both groups. Although some minimum variations were notable across the two groups, some positive and significant correlations between entrepreneurship education and technological creativity, on one hand, and the direct determinants of entrepreneurship intentions and actual entrepreneurship intentions, on the other, were revealed for both groups of students. The findings also provided strong support to the view that entrepreneurship education and technological creativity jointly predict the antecedents of entrepreneurship intention but have a non-significant direct relationship with actual entrepreneurship intentions. Lastly, all the immediate determinants of entrepreneurship intentions, except for subjective norms, significantly predict entrepreneurship intentions of South African and Zimbabwean tertiary students. To a large extent, the results validated the Theory of Planned Behaviour as a guiding tool for estimating any premeditated entrepreneurial behaviour. Thus, the Theory remains an invaluable theoretical lens for academics, educators and policy-makers’ evaluation of effective ways of enhancing the grooming of potential entrepreneurs. The theoretical contribution of this study lies in its introduction of a novel, previously untested construct, technological creativity, to the Theory of Planned Behaviour, to unravel the complexity of entrepreneurial intentions among tertiary students in a comparative country-based study. Based on the significant joint effects of entrepreneurship education and technological creativity on the direct determinants of entrepreneurship intentions, the study recommends the infusion of technological creativity into entrepreneurship education courses at tertiary institutions in Zimbabwe and South Africa.
Pubished Thesis